Studi Fenomenologis Tentang Implementasi Tata Kelola Perguruan Tinggi Badan Hukum di Indonesia - Yusar Sagara; Santi Yustini (Akuntabilitas, 2019)
This study examines the laws and regulations that form the legal basis of governance of state universities and their implications for academic and non-academic autonomy. The purpose of this study is to find answers to policies and practices of academic and non-academic governance and find alternative support of university management concepts and practices from the study of laws and regulations on higher education and legislation on state finance. Data analysis is using qualitative by studying the ideal concept (according to regulation, observation and documentation). The results of this study conclude that the governance of state universities in the context of academic autonomy is still too dominated by the government. In non-academic autonomy is also not yet fully implemented such as organizational structure, staffing, finance, and international cooperation.